METAPHORICAL CONCEPTS AND THEIR IDEOLOGICAL FUNCTIONS IN ALURING VOTES FOR INDONESIAN PRESIDENCY - Budiman, Arif; Khristianto, Khristianto (Lire Journal (Journal of Linguistics and Literature), 2024)
This study is to reveal the metaphor used in political talks among the supporters of running mates in Indonesian General Election of 2019, those are Jokowi as the incumbent, and Prabowo as the competitor. This applied a content analysis to explore the use of metaphor in the political speeches. The data source included the news and the videos containing metaphors produced by the politician supporting the candidates. The theory applied in investigating the metaphors are conceptual metaphor (Lakoff and Johnson:1980), and the Critical Metaphor Analysis, CMA (Charteris-Black: 2004). Some conceptual metaphors drawn from their metaphorical expressions are NATION IS A BUILDING, functions to criticize that the building couldn’t stand on the lie, hiding the history of competitor candidate, Prabowo. Other metaphors from the incumbent are targeted to Rocky Gerung (RG), as a tough and intelligent speakers in Indonesian political discourse. Budiman Sujatmiko took the concept of DEBATING IS A PLAY, undermining the arguments in RG’s statements. Meanwhile, the supporters in Prabowo Camp focuses on criticizing the behavior of the existing government and leaders, by creating concepts of MISUSING IS STEALING, PRESIDENT IS A SCHOOL BOY, SWEARING IS A SENSATION, TO LEAD IS TO SUFFER. These two different metaphors go into an ideology with different direction. In one side, the incumbents claim that the government has failed. In another, the opposants believe that it has failed, by proving their bad behaviors